2013
DOI: 10.1080/09712119.2013.825619
|View full text |Cite
|
Sign up to set email alerts
|

Early immune gene expression responses toSalmonella enteritidisinfection in indigenous chickens

Abstract: Salmonella enteritidis (SE) is a common cause of food-borne disease in humans and loss of growth in poultry. An effective method to inhibit salmonellosis is to increase the genetic resistance of poultry to Salmonella through genetic selection programmes that may be performed using phenotypic or genotypic data. A better understanding of the effects of Salmonella infection on the expression of inflammatory and anti-infectious cytokines and antimicrobial molecules is essential for choosing potential markers in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…If Salmonella are still capable of surviving in macrophages, T cells are promoted to move to the avian gut mucosa (Berndt et al 2007;Van Hemert 2007). Early expression of cytokines, chemokines and apoptotic molecules in the chicken intestine has been reported in previous studies (Cheeseman et al 2007;Van Hemert 2007;Tohidi et al 2013b). The amount of CD4 + T-cells did not increase 1, 5 and 7 days pi with SE.…”
Section: Gene Expression Response To Salmonella In Intestinesupporting
confidence: 68%
See 1 more Smart Citation
“…If Salmonella are still capable of surviving in macrophages, T cells are promoted to move to the avian gut mucosa (Berndt et al 2007;Van Hemert 2007). Early expression of cytokines, chemokines and apoptotic molecules in the chicken intestine has been reported in previous studies (Cheeseman et al 2007;Van Hemert 2007;Tohidi et al 2013b). The amount of CD4 + T-cells did not increase 1, 5 and 7 days pi with SE.…”
Section: Gene Expression Response To Salmonella In Intestinesupporting
confidence: 68%
“…Interfron γ transcripts were higher in the spleen than in the caecum of chickens inoculated with SE 18 h pi (Cheeseman et al 2007). However, NRAMP1 was commonly increased in the caecum and spleen of SE-challenged chickens 48 h pi, whereas TLR4, IL8 and IFNγ were only upregulated in the caecum at the same time (Tohidi et al 2013b). Microarray analysis revealed 272 genes that were significantly up-regulated on day 7 pi with SE and 490 genes on day 8 in high splenic SE burden compared to unchallenged chickens.…”
Section: Gene Expression In Systemic Organsmentioning
confidence: 97%
“…Enteritidis ( 16 ). The role of heterophils was not considered in the current study, but increases in CXCLi2 expression have been reported in various cells and tissue types across diverse breeds of chickens ( 45 47 ). Therefore, our study is in agreement and indicates increased CXCLi2 is likely a contributing factor to the lower numbers of bacteria seen at the early time.…”
Section: Discussionmentioning
confidence: 99%